2020
DOI: 10.1182/blood-2020-140117
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Short Chain Fatty Acids As a Predictor of Response to Therapy for Life-Threatening Acute Graft-Versus-Host Disease

Abstract: Introduction Minnesota High Risk and steroid-refractory acute graft-versus-host disease (aGVHD) are life-threatening complications of allogeneic hematopoietic cell transplantation (HCT). Recent data suggests dysbiosis may relate to GVHD outcomes. Bacteria in the lower gastrointestinal tract (LGI) produce short chain fatty acids (SCFAs) as fuel for enterocytes and modulators of mucosal immunity. LGI damage caused by aGVHD and antibiotic administration may be detrimental to SCFAs production and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…butyrate) to be associated with protection from chronic GvHD (53). Further, SCFAs might be used as a predictor of therapeutic efficacy against acute GvHD: patients responding to acute GvHD treatment displayed higher plasma SCFA concentrations compared to non-responders (54). This is underlined by a study based on infants, which found antibiotic treatment and reduced SCFA production to be linked to an increased gut GvHD risk (55).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…butyrate) to be associated with protection from chronic GvHD (53). Further, SCFAs might be used as a predictor of therapeutic efficacy against acute GvHD: patients responding to acute GvHD treatment displayed higher plasma SCFA concentrations compared to non-responders (54). This is underlined by a study based on infants, which found antibiotic treatment and reduced SCFA production to be linked to an increased gut GvHD risk (55).…”
Section: Lipid Metabolismmentioning
confidence: 99%